The antiracist kitchen : 21 stories (and recipes) - Rogers, Andrea L.; De Leon, Jennifer, 1979-; Mather, Janice Lynn; Rice, Waubgeshig, 1979-; Ali, S. K.; Avery, Bryan Patrick; Deen, Natasha; Loney, Andrea J.; Park, Linda Sue; Ramadan, Ahmad Danny; Chan, Marty; Grande, Reyna; et al. (Orca Books Publishers, 2023)
"This illustrated nonfiction anthology is a collection of stories and recipes about antiracism from 21 North American children's authors."--